[PP.22.16] APPLE POLIPHENOLS EFFECTS ON ENDOTHELIAL REACTIVITY AND SERUM URIC ACID: FROM PRECLINICAL DATA TO A DOUBLE BLIND-RANDOMIZED CLINICAL TRIAL. (September 2017) - A.F.G. Cicero; Caliceti, C.; Fogacci, F.; Calabria, D.; Giovannini, M.; Rosticci, M.; Roda, A.; Borghi, C.
Abstract : Objective: Several studies support a beneficial role of the dietary polyphenols in regulating some cardiovascular risk factors. The objective of our study was to examine the apple polyphenols' proprieties. Design and method: This was a two-phases study. The in vitro experiment was carried out developing a sensitive method measuring the intracellular xantine oxidase [XO] activity and its inhibition due to drugs effectively able to cross the cell membrane. A reaction mixture without XO was used as negative control and one with several diluition of oxypurinol was used as positive control. The in vivo study consisted in a randomized, double-blind, parallel placebo-controlled clinical trial involving 60 volunteers withsuboptimal values of fasting plasma glucose (101 mg/dL < FPG < 126 mg/dL). The treatment period was 8 weeks long and consisted in an indistinguishable pill of placebo or an active product, containing 300 mg of apple polyphenol extract. Results: The inhibition degree of XO by apple polyphenols was IC50 = 154 ± 28 ng/mL. During the clinical trial, after the first four weeks of treatment, the FPG decreased in the active treated group (−6, 1%, P < 0, 05), while no significant changes were observed in both groups of treatment regarding the other hematochemistry parameters or the blood pressure values and the anthropometric characteristics (P > 0, 05 always). After 8 weeks of treatment, the active-treated patients had an improvement in the FPG compared to the baseline (−10, 3%, P < 0, 001) and the placebo group (P < 0, 001) and SUA significantly improved too (−14, 0%, P < 0, 05 vs baseline; P < 0, 05 vs placebo). Also the endothelial reactivity increased in the actively treated subjects in comparison with the baseline (0, 24 ± 0, 09, P = 0, 009) and the placebo-treated group (P < 0, 05). Conclusions: In vivo, apple polyphenols have a positive effect on the vascular oxidative stress and the endothelium function and reduce FPG and uric acid by the inhibition of the XO, as our in vitro experiment attests.